Ultrahigh pressure synthesis of highly efficient FeNx/C electrocatalysts for the oxygen reduction reaction. Issue 33 (8th August 2017) - Guo, Xin; Jia, Xiaopeng; Song, Ping; Liu, Jing; Li, Erling; Ruan, Mingbo; Xu, Weilin
Abstract : An ultrahigh pressure (UHP) method was employed to rapidly synthesize (5 min) a high-efficiency ORR FeN x /C catalyst for the first time. Abstract : Ultrahigh pressure (UHP) was employed for the first time as a green method for the synthesis of highly efficient Fe, N co-doped carbon-based (FeN x /C) electrocatalysts for the oxygen reduction reaction (ORR). Compared with traditional pyrolysis under atmospheric conditions, the synthesis of FeN x /C catalysts under UHP could be done efficiently with much less consumption of time, energy and chemicals. The observed highly efficient synthesis and high ORR activity of such catalysts could be due to the fast heating system (12 °C per second) under UHP, which leads to highly efficient doping of heteroatoms on carbon with much less consumption of chemicals and energy; the UHP-induced high graphitization degree of the carbon support and the selective formation of highly active sites of pyridinic N and Fe–N x for the ORR also contribute in part to the high ORR catalytic activity of the catalyst. The work presented here paves a new way for the green, environmentally friendly synthesis of heteroatom-doped highly efficient catalysts for energy or chemical processes.